Tra vuoto e movimento: ‘indizi di nuove economie’ che disegnano traiettorie per il progetto di territorio. Nuovi abitanti a Luogosanto - Lutzoni, Leonardo (Scienze del Territorio, 2014)
Starting from the first-person narrative of the life stories of two ‘new inhabitants’ settled down in the Municipality of Luogosanto, located in the region of high Gallura, northern Sardinia, who took up new economies linked to earth and territory, the article describes possible trajectories (immediately existential, political and programming in a perspective view) along which try to combine economic growth, social cohesion, environmental protection and enhancement of territories, relying on the aggregation of local elements and global. Paths in which the new inhabitants, capable of awakening and disseminating a new and ancient ‘territorial awareness’, play a key role as protagonists of this transformation.